The Importance of Teaching A Foreign Language to Children of Preschool and Younger Educational Age - Nazarova Ma’rifat Abduraim qizi; Jumanazarov Umid (Scientific Trends, 2023)
This article discusses the importance of teaching a foreign language to children of preschool and primary school age.
Keywords: Foreign language ,education ,preschool ,primary constructive,approach,point of view.